Rescue of a Vaccinia Virus Mutant Lacking IFN Resistance Genes K1L and C7L by the Parapoxvirus Orf Virus - Riad, Sherief; Xiang, Yan; AlDaif, Basheer; Mercer, Andrew A.; Fleming, Stephen B. (Frontiers in Microbiology, 2020)
Type 1 interferons induce the upregulation of hundreds of interferon-stimulated genes (ISGs) that combat viral replication. The parapoxvirus orf virus (ORFV) induces acute pustular skin lesions in sheep and goats and can reinfect its host however, little is known of its ability to resist IFN. Vaccinia virus (VACV) encodes a number of factors that modulate the IFN response including the host-range genes C7L and K1L. A recombinant VACV-Western Reserve (WR) strain in which the K1L and C7L genes have been deleted does not replicate in cells treated with IFN-β nor in HeLa cells in which the IFN response is constitutive and is inhibited at the level of intermediate gene expression. Furthermore C7L is conserved in almost all poxviruses. We provide evidence that shows that although ORFV is more sensitive to IFN-β compared with VACV, and lacks homologues of KIL and C7L, it nevertheless has the ability to rescue a VACV KIL- C7L- gfp+ mutant in which gfp is expressed from a late promoter. Co-infection of HeLa cells with the mutant and ORFV demonstrated that ORFV was able to overcome the block in translation of intermediate transcripts in the mutant virus, allowing it to progress to late gene expression and new viral particles. Our findings strongly suggest that Orf virus encodes a factor(s) that, although different in structure to C7L or KIL, targets an anti-viral cellular mechanism that is a highly potent at killing poxviruses.